Comparative Evaluation of Efficacy of Physics Forceps Versus Conventional Forceps in Orthodontic Extractions - Farhan Javed, Atiq Ur Rahman, Muhammad Afzal, Khaqan Azam, Waqar Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To comparative evaluation of efficacy of physics forceps versus conventional forceps in orthodontic extractions. Design of the Study: It was a cross-sectional survey. Place and Duration of Study: This study was carried at Department of Maxillofacial Surgery Mufti Mehmood Teaching Hospital Dera Ismail Khan from January 2022 to June 2022. Patients and Methods: Total 300 healthy patients reporting to our department and who were indicated for removal of tooth with ideal extraction indications and conditions, and consenting for the same were taken up for the study. Patients were divided into 2 groups: Group-1 consisted of a split mouth study with 100 patients and Group-2 consisted of 200 patients consecutively selected and further categorised randomly, were subdivided into 2 subgroups, Group-2A (Conventional forceps group) and Group-2B (Physics forceps group) with 100 patients each. All the extraction procedures were done by 2 operators namely A and B & an experienced observing assistant was used for the assessment of Operative complications. Every patient underwent an adequate pre-surgical preparation consisting of adequate case history, gross scaling, blood test where indicated and radiographic examination. Results of the Study: In Group-1 the average time taken with physics forceps was 33.14 seconds with a SD of 12.272 seconds and the average time taken with conventional forceps was 53.86 seconds with a SD of 24.985 seconds. In Group-2 the average time taken with physics forceps was 24.77 seconds with a SD of 9.878 seconds and the average time taken with conventional forceps was 34.78 seconds with a SD of 8.693 seconds. In Group-1 on 3rd post-operative day, with Conventional forceps the mean pain score was 6.45 and with Physics forceps the mean pain score was 4.15. In Group-2, on 3rd post-operative day, with Conventional forceps the mean pain score was 6.46 and with Physics forceps the mean pain score was 3.75. Conclusion: Physics forceps are comparatively superior to conventional extraction forceps in terms of lesser time taken for the procedure, lesser tendency to induce trauma to both hard and soft tissue and have been found to induce comparatively lesser pain post extraction. Keywords: Bone loss, Extraction forceps, Physics forceps, Soft tissue loss